2022
DOI: 10.3390/foods11182827
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Rutin–Loaded Zein–Carboxymethyl Starch Nanoparticles

Abstract: In this work, rutin (RT)–loaded zein–carboxymethyl starch (CMS) nanoparticles were successfully prepared by the antisolvent precipitation method. The effect of CMS on composite nanoparticles at different concentrations was studied. When the ratio of zein–RT–CMS was 10:1:30, the encapsulation efficiency (EE) was the highest, reaching 73.5%. At this ratio, the size of the composite nanoparticles was 196.47 nm, and the PDI was 0.13, showing excellent dispersibility. The results of fluorescence spectroscopy, FTIR,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
12

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 76 publications
1
4
0
12
Order By: Relevance
“…Rutin (RT), a flavonoid, also called vitamin P, can be found in a wide variety of foods, including apples (350 to 4780 μg/g), citrus fruits (2.7 to 8106.7 µg/g), and tea (303 to 479 μg/g) [ 3 ]. Rutin is an important metabolite of Ruta graveolens [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rutin (RT), a flavonoid, also called vitamin P, can be found in a wide variety of foods, including apples (350 to 4780 μg/g), citrus fruits (2.7 to 8106.7 µg/g), and tea (303 to 479 μg/g) [ 3 ]. Rutin is an important metabolite of Ruta graveolens [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The FT-IR results showed that compared to PDA, a new peak at 2,890 cm −1 was observed in PP group, indicating that PEG is bound to PDA. 19 Furthermore, a new peak at approximately 3,400 cm −1 , belonging to the hydroxyl stretching vibration of rutin, 20 was observed in the PRP group ( Figure 1 D), indicating that rutin was successfully loaded onto the PP NPs. Similarly, the UV-Vis spectra showed a characteristic absorption peak at 359 nm for PPR NPs, indicating the successful binding of rutin to PP NPs ( Figure 1 E).…”
Section: Resultsmentioning
confidence: 95%
“…Nanocarreadores também podem estimular a penetração e distribuição do dsRNA na planta (WU; LI, 2022;YONG et al, 2022), o que poderia ser útil para controle de insetos-praga sugadores de seiva, minadoras de folhas, caules ou consumidores de raízes .…”
Section: Dsrna Sintético Associado a Nanocarreadoresunclassified
“…A dimensionalidade de um nanocarreador é uma importante característica no que se diz respeito ao desenvolvimento de sistemas de entrega de biopesticidas à base de dsRNA (Figura 5) . A dimensão do nanocarreador pode influenciar a eficiência da entrega do dsRNA ao inseto e a penetração e translocação nas plantas (HU;LI, 2022;. Nanomateriais de zero dimensão (0-D) apresentam todas as suas três dimensões na escala nanométrica, o que os tornaria mais eficientes na passagem pela membrana peritrófica do intestino dos insetos e na penetração e transporte nas plantas LINKE et al, 2022;SINGH et al, 2022).…”
Section: Dsrna Sintético Associado a Nanocarreadoresunclassified
See 1 more Smart Citation